Role of Moesin Phosphorylation in Retinal Pericyte Migration and Detachment Induced by Advanced Glycation Endproducts - Zhang, Shuang-Shuang; Hu, Jia-Qing; Liu, Xiao-Hui; Chen, Li-Xian; Chen, Hong; Guo, Xiao-Hua; Huang, Qiao-Bing (Frontiers in Endocrinology, 2020)
Proliferative diabetic retinopathy (PDR) involves persistent, uncontrolled formation of premature blood vessels with reduced number of pericytes. Our previous work showed that advanced glycation endproducts (AGEs) induced angiogenesis in human umbilical vein endothelial cells, mouse retina and aortic ring, which was associated with moesin phosphorylation. Here we investigated whether moesin phosphorylation may contribute to pericyte detachment and the development of PDR. Primary retinal microvascular pericytes (RMPs) were isolated, purified from weanling rats, and identified by cellular markers α-SMA, PDGFR-β, NG2 and desmin using immunofluorescence microscopy. Effects of AGE-BSA on proliferation and migration of RMPs were examined using CCK-8, wound healing and transwell assays. Effects on moesin phosphorylation were examined using western blotting. The RMP response to AGE-BSA was also examined when cells expressed the non-phosphorylatable Thr558Ala mutant or phospho-mimicking Thr558Asp mutant of moesin or were treated with ROCK inhibitor Y27632. Colocalization and interaction between CD44, phospho-moesin and F-actin were observed. Experiments with cultured primary RMPs showed that AGE-BSA inhibited the proliferation, enhanced the migration, and increased moesin phosphorylation in a dose- and time-dependent manner. AGE-BSA also triggered the rearrangement of F-actin and promoted the interaction of CD44 with phospho-moesin in RMPs. These effects were abrogated in cells expressing the non-phosphorylatable moesin mutant and the application of ROCK inhibitor Y27632 attenuated AGE-induced alteration in cultured RMPs by abolishing the phosphorylation of moesin. However, those AGE-induced pathological process occurred in RMPs expressed the phospho-mimicking moesin without AGE-BSA treatment. It is concluded that AGEs could activate ROCK to mediate moesin phosphorylation at Thr558, and resulting phospho-moesin interacts with CD44 to form CD44 cluster, which might stimulate the migration of RMPs and subsequent RMP detachment in microvessel. This pathway may provide new drug targets against immature neovessel formation in PDR.